2014
DOI: 10.3171/2014.9.spine13667
|View full text |Cite
|
Sign up to set email alerts
|

Functional variability of sacral roots in bladder control

Abstract: Object Sacral roots are involved in sensory, autonomic, and motor innervation of the lower limbs and perineum. Theoretically, it can be assumed that the S-3 root level innervates the bladder; however, clinical practice shows that this distribution can vary. Few researchers have studied this variability. Methods The authors conducted a retrospective study involving 40 patients who underwent surgery requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A direct ventral sacral root electrical stimulation study measuring bladder contraction by means of intravesical pressure showed that in 100% of the patients, bladder pressure increase was measured upon stimulation of the S3 anterior sacral root, but also in 60%, upon stimulation of S4, 40% on S2 and around 15% at S5. There is an individual difference in distribution of bladder efferent fibers . It is unknown if the distribution of motor nerves activated directly by neurostimulation is similar to the distribution of the rootlets stimulated for the indirect neuromodulation effect.…”
Section: Implant Techniquementioning
confidence: 52%
See 1 more Smart Citation
“…A direct ventral sacral root electrical stimulation study measuring bladder contraction by means of intravesical pressure showed that in 100% of the patients, bladder pressure increase was measured upon stimulation of the S3 anterior sacral root, but also in 60%, upon stimulation of S4, 40% on S2 and around 15% at S5. There is an individual difference in distribution of bladder efferent fibers . It is unknown if the distribution of motor nerves activated directly by neurostimulation is similar to the distribution of the rootlets stimulated for the indirect neuromodulation effect.…”
Section: Implant Techniquementioning
confidence: 52%
“…There is an individual difference in distribution of bladder efferent fibers. 127 It is unknown if the distribution of motor nerves activated directly by neurostimulation is similar to the distribution of the rootlets stimulated for the indirect neuromodulation effect.…”
Section: Leads That Require Higher Thresholds or Offer Responses At Fmentioning
confidence: 99%
“…A lead is implanted in S4, instead of S3, when the best bellows response upon lead stimulation is elicited at this location. This could be explained by the fact that sacral spinal nerves are mixed nerves and show great variability in their functional distribution . The foraminal level, therefore, seems less important than placement inside a foramen leading to an adequate bellows response upon stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Carlucci et al [14] found a significant horizontal and vertical variability in the functional distribution of sacral roots in bladder innervation. These findings help us to understand the variability in cauda equina syndrome.…”
Section: Discussionmentioning
confidence: 99%